Regional polarization in Turkey - Yilmaz, Ensar; Kaplan, Zeynep (WILEY, 2022)
In this study using household data, we aim to track the trends in regional income polarization in Turkey and focus on the extent of and trends in regional income disparity. With the help of classical and newly developed indexes and decomposition methodologies, we estimate the polarization level, temporal trends and the decomposition within and between regions of the western and eastern regions in Turkey. We also analysed the impact of being in the east or in the west on income polarization, controlling for other individual and household characteristics. To shed more light on the underlying mechanisms behind the polarization between two regions, we performed an ordered logit regression.
Keywords: EUROPEAN REGIONS; INTERREGIONAL INEQUALITY; INCOME INEQUALITY; WAGE INEQUALITY; CROSS-COUNTRY; CONVERGENCE; GROWTH; DYNAMICS; CANADA; Development Studies; Public Administration